Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/0022034519827590
|View full text |Cite
|
Sign up to set email alerts
|

ACC Plasticity Maintains Masseter Hyperalgesia Caused by Occlusal Interference

Abstract: Acute occlusal interference following improper occlusal alteration in dental practice can induce chronic masticatory muscle pain. The underlying mechanism has not been clarified. Synaptic plasticity in the anterior cingulate cortex (ACC) plays a key role in the chronic pain state. This study investigated the role of synaptic plasticity in the ACC in acute occlusal interference–induced chronic masticatory muscle pain. A rat model of experimental occlusal interference (EOI) was established. In vivo local field p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…These human data provide an excellent starting point for reverse translational approaches to determine detailed neural circuit mechanisms of craniofacial muscle pain in the brains of experimental animals. For example, a recent study showed that enhanced synaptic transmission in ACC, as evaluated by stimulating the medial thalamus, was shown to maintain long-lasting masseter hyperalgesia induced by occlusal interference in rats (Xu et al 2019).…”
Section: Maladaptive Changes Of Pain Circuits In the Brainmentioning
confidence: 99%
“…These human data provide an excellent starting point for reverse translational approaches to determine detailed neural circuit mechanisms of craniofacial muscle pain in the brains of experimental animals. For example, a recent study showed that enhanced synaptic transmission in ACC, as evaluated by stimulating the medial thalamus, was shown to maintain long-lasting masseter hyperalgesia induced by occlusal interference in rats (Xu et al 2019).…”
Section: Maladaptive Changes Of Pain Circuits In the Brainmentioning
confidence: 99%
“…Increased medial thalamus (MT) stimulation steadily elicited gradually enhanced local field potential (LTP) amplitudes in the ACC of control and EOI rats. Rats that received EOI for 14 and 21 d exhibited dramatically enhanced LFP in the ACC in response to MT stimulation, in comparison with control rats and rats that received EOI for 7 d. The results suggest that MT‐ACC synaptic transmission was potentiated since 14 d after EOI application 68 …”
Section: Introductionmentioning
confidence: 77%
“…9,46 Other CNS areas involved in the descending pain-modulatory systems such as the ACC may also have participated in the maintenance of pain on postoperative day 14 induced by PEOI although our earlier study suggests that the ACC may have not been involved in the maintenance of hyperalgesia following late EOI removal on postoperative day 8, which more likely involves mainly the descending facilitatory influence of RVM ON-cells. 10,11 Undoubtedly, there are complex interactions between EOI-related nociceptive inputs and the RVM as well as higher brain areas involved in descending modulation of nociceptive transmission, 12,13,15,18 and further studies are needed to unravel these interactions, including the role of glioplasticity as well as neuroplasticity in the RVM.…”
Section: On-and Off-cell Activity Following Reoi On Day 8 and Effect Of Cbxmentioning
confidence: 99%
“…The possible mechanisms underlying the PEOI-induced hyperalgesia were suggested to include neuronal and glial activation in the medullary dorsal horn (MDH) 9 and potentiation of synaptic transmission in the thalamus to the anterior cingulate cortex (ACC). 10 Also noteworthy are our recent findings that adaptive neuroplasticity of ON-and OFF-cells in the rostral ventromedial medulla (RVM) participated in the chronification, maintenance and inhibition of the PEOI-induced oro-facial hyperalgesia. 11 The RVM is part of the descending pain modulation system which exerts 'top-down' control on ascending nociceptive transmission.…”
Section: Introductionmentioning
confidence: 99%